2015
DOI: 10.1179/1743285515y.0000000016
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and processing of zircon from Murray Basin mineral sand deposits

Abstract: Mineral sand deposits in the Murray Basin offer the potential for significantly expanding Australia's production of ilmenite, rutile and zircon. Since prices of zircon and rutile are higher than ilmenite, and zircon grades in most deposits are significantly higher than those for rutile, zircon often is the major economic mineral component in mineral sand deposits. Two types of deposits occur in the Murray Basin. They comprise strandline deposits, in which the particle size of the heavy minerals is similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
(33 reference statements)
0
25
0
Order By: Relevance
“…To fulfill such a requirement, the zircon sand needs to be improved by separating the ZrO 2 from its impurities using magnetic separator and tabling. No radioactive minerals detected by XRF instrument (Pownceby et al, 2015).…”
Section: Resultsmentioning
confidence: 93%
“…To fulfill such a requirement, the zircon sand needs to be improved by separating the ZrO 2 from its impurities using magnetic separator and tabling. No radioactive minerals detected by XRF instrument (Pownceby et al, 2015).…”
Section: Resultsmentioning
confidence: 93%
“…In the dry mill, valuable minerals are separated from non-valuable minerals (mostly quartz) using physical properties (Table 1 ). In addition, Pownceby et al ( 2015 ) demonstrated the use of flotation for HM separation, and Freeman and Sparrow ( 1999 ) suggested ultra-sonic techniques to replace high-intensity magnetic separation. The processing of HM sands uses comparatively fewer chemicals such as floatation aids and is thus more environmentally friendly than other mineral industries (Gilman 2008 ).…”
Section: Mining Of Hmsmentioning
confidence: 99%
“…≤100 ppm. Zircon concentrates extracted from the Tista River should therefore have equivalent or lower radiogenic content than those from beach sand deposits that are conventionally mined for zircons, such as the Cox's Bazar region in Bangladesh (100-500 ppm Th, ∼100 ppm U in Zaman et al 2016) or the Murray Basin deposit in Australia (∼500 ppm Th, 500 ppm U, in Pownceby et al 2015).…”
Section: Mineral Abundance and Elemental Deportmentmentioning
confidence: 99%